The Application of Stimulus-Organism-Response (SOR) Theory for Studying Workforce Contributions in the Pineapple Factories in Chiang Rai - Pyo, Nang Herk Leng (International Journal of Multidisciplinary in Management and Tourism, 2022)
In this study the SOR (Stimulus Organism Response) theory that is typically used in consumer behaviors is employed for workforce contribution study of organizational performance, which exploits the theories of job demand-resources (JD-R), motivation and trust as stimuli. The conceptualized model was empirically tested using the phu-lae and nang-lae pineapple manufacturers and traders in the Thasud, Ban Du and Nang Lae districts of Chiang Rai. The surveys were conducted in September-October 2019, which is the low-production season. The structural equation modeling (SEM) analysis shows perfect fits, evidenced with Normed Fit Index (NFI), Comparative Fit Index (CFI), Tucker Lewis Index all closer to 1.0, and RMSEA at 0.051, and the livelihood minimization shows absolute model fit, at p = 0.282, which is p > 0.05, at /2 = 1.251, much below the threshold number, 5.